2015
DOI: 10.1016/j.jml.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Phonological neighborhood competition affects spoken word production irrespective of sentential context

Abstract: Two experiments examined the influence of phonologically similar neighbors on articulation of words’ initial stop consonants in order to investigate the conditions under which lexically-conditioned phonetic variation arises. In Experiment 1, participants produced words in isolation. Results showed that the voice-onset time (VOT) of a target’s initial voiceless stop was predicted by its overall neighborhood density, but not by its having a voicing minimal pair. In Experiment 2, participants read aloud the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 76 publications
6
30
0
Order By: Relevance
“…Using the presence or absence of minimal pair voicing contrasts as a proxy for lexical density, behavioral results show longer VOT values for words beginning with voiceless stop consonants that have voiced minimal pairs compared to words that do not (e.g. t ense-dense vs. t enth, *denth is not a word) (Baese-Berk & Goldrick, 2009; Fox, Reilly, & Blumstein, 2015). Peramunage et al (2011) examined the neural substrates of this lexically conditioned phonetic variation and showed cascading activation throughout the spoken word production system with modulatory effects under these conditions in the posterior superior temporal and supramarginal gyri (implicated in phonological and lexical selection), the inferior frontal gyrus (implicated in phonological planning) and the precentral gyrus (implicated in articulatory processes) (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Using the presence or absence of minimal pair voicing contrasts as a proxy for lexical density, behavioral results show longer VOT values for words beginning with voiceless stop consonants that have voiced minimal pairs compared to words that do not (e.g. t ense-dense vs. t enth, *denth is not a word) (Baese-Berk & Goldrick, 2009; Fox, Reilly, & Blumstein, 2015). Peramunage et al (2011) examined the neural substrates of this lexically conditioned phonetic variation and showed cascading activation throughout the spoken word production system with modulatory effects under these conditions in the posterior superior temporal and supramarginal gyri (implicated in phonological and lexical selection), the inferior frontal gyrus (implicated in phonological planning) and the precentral gyrus (implicated in articulatory processes) (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, VOT was longer for words that had a voiced minimal pair (e. g. tart-dart) compared to ones that did not (e. g. tar; *dar is not a word). Further behavioral work in our lab showed that this lexically-conditioned variation was actually driven by overall lexical density, not by the presence or absence of a voiced minimal pair (Fox, Reilly & Blumstein, 2015). In this study, participants read words either in isolation or in biased or neutral contexts.…”
Section: Segments Features and The Lexiconmentioning
confidence: 68%
“…Here, VOT was used as a proxy for lexical density (see Fox, Reilly & Blumstein, 2015 for discussion). That is, words beginning with voiceless stop consonants that had voiced minimal pair competitors were from high density neighborhoods and voiceless stop consonants that did not have voiced minimal pairs were from low density neighborhoods.…”
Section: Segments Features and The Lexiconmentioning
confidence: 99%
“…Note that this may underestimate individual differences. A random intercept by word was also included to model potential differences in VOT according to word-level factors like neighbourhood density (Goldinger and Summers, 1989;Fox et al, 2015). We examined the improvement to model fit of including the random talker intercepts using a likelihood ratio test (χ 2 ) comparing models with just the random word intercept and models including both intercepts (see also Kliegl et al, 2011, for discussion of using random effects to examine individual differences).…”
Section: Individual Differences In Individual Cuesmentioning
confidence: 99%